Use of Heading Direction for Recreating the Horizontal Alignment of an Existing Road. (3rd February 2015) - Camacho‐Torregrosa, Francisco J.; Pérez‐Zuriaga, Ana M.; Campoy‐Ungría, José M.; García, Alfredo; Tarko, Andrew P.
Abstract This article proposes a new method for fitting the horizontal alignment of a road to a set of (x, y) points. Those points can be obtained from digital imagery or GPS‐data collection. Unlike current methods that represent road alignment through its curvature, the proposed method describes the horizontal alignment as a sequence of headings. An analytic–heuristic approach is introduced. The proposed method produces unique solutions even for complex horizontal alignments. Some examples and a case study are presented. This solution may not be accurate enough for road redesign, but it allows researchers and departments of transportation to obtain accurate geometric features.